HUBUNGAN ANTARA JUMLAH LEUKOSIT DENGAN MOTILITAS SPERMATOZOA PADA ANALISIS SEMEN PRIA DI SAMMARIE FAMILY HEALTHCARE JAKARTA JANUARI - AGUSTUS 2019 - Wanodia Ayutama, (2020)
Infertility is one of the most common male reproductive health problems. Men with poor sperm quality are more susceptible to infertility. One of the cause of infertility in men is disruption of spermatozoa motility. Imperfect motility will reduce the probability of conception. One cause of decreased motility is inflammation of the male reproductive tract. Inflammation that occurs will increase the recruitment of leukocytes in the reproductive tract so it can interfere the process of sperm formation and maturation. The purpose of this study was to determine the relationship between leukocyte counts and spermatozoa motility. The number of leukocytes and the percentage of spermatozoa motility were obtained from semen analysis as secondary data. The research design used was cross-sectional. The number of samples in this study were 66 respondents who met the inclusion criteria.The results of the study showed a significant inverse relationship (negative correlation) (p = 0.007, r = -0.328) between the number of leukocytes and spermatozoa motility, which means if the number of semen leukocytes increases, the percentage of spermatozoa motility will decrease.